Eradication of Potato Virus S, Potato Virus A, and Potato Virus M From Infected in vitro-Grown Potato Shoots Using in vitro Therapies - Bettoni, Jean Carlos; Mathew, Liya; Pathirana, Ranjith; Wiedow, Claudia; Hunter, Donald A.; McLachlan, Andrew; Khan, Subuhi; Tang, Joe; Nadarajan, Jayanthi (Frontiers in Plant Science, 2022)
Certain viruses dramatically affect yield and quality of potatoes and have proved difficult to eradicate with current approaches. Here we describe a reliable and efficient virus eradication method that is high throughput and more efficacious at producing virus-free potato plants than current reported methods. Thermotherapy, chemotherapy and cryotherapy treatments were tested alone and in combination for ability to eradicate single and mixed Potato virus S (PVS), Potato virus A (PVA), and Potato virus M (PVM) infections from three potato cultivars. Chemotherapy treatments were undertaken on in vitro shoot segments for four weeks in culture medium supplemented with 100 mg L-1 ribavirin. Thermotherapy on in vitro shoot segments was applied for two weeks at 40°C (day) and 28°C (night) with a 16 h photoperiod. Plant vitrification solution 2 (PVS2) and cryotherapy treatments included a shoot tip preculture followed by exposure to PVS2 either without or with liquid nitrogen (LN, cryotherapy) treatment. The virus status of control and recovered plants following therapies was assessed in post-regeneration culture after three months and then retested in plants after they had been growing in a greenhouse for a further three months. Microtuber production was investigated using in vitro virus-free and virus-infected segments. We found that thermotherapy and cryotherapy (60 min PVS2 +LN) used alone were not effective in virus eradication, whilst chemotherapy was better but with variable efficacy (20% to 100%). The most effective result (70%–100% virus eradication) was obtained by combining chemotherapy with cryotherapy, or by consecutive chemotherapy, combined chemotherapy and thermotherapy, then cryotherapy treatments irrespective of cultivar. Regrowth following the two best virus eradication treatments was similar ranging from 8.6% to 29% across the three cultivars. The importance of virus removal on yield was reflected in ‘Dunluce’ free of PVS having higher numbers of microtubers, and in ‘V500’ free of PVS and PVA, having a greater proportion of microtubers > 5 mm. Our improved procedure has potential for producing virus-free planting material for the potato industry. It could also underpin the global exchange of virus-free germplasm for conservation and breeding programs.